Разработка оптимизированной методики расчета волновых прецессионных передач с телами качения - Маргулис, Михаил Владимирович; Гордиенко, Ярослав Олегович (НТУ "ХПИ", 2016)
Предложена оптимизированная методика расчета волновых прецессионных передач с телами качения. Методика комплексно учитывает особенности геометрии передач, используемые материалы, твердость поверхностного слоя основных звеньев и рациональную долговечность передач. Геомегрические параметры периодических дорожек качения и тел качения оптимизированы по критерию минимальных контактных напряжений и потерь на трение. Приведен пример расчета.

Optimized methodics of calculation of harmonic precessional drives with rolling elements is given. This complex considers the specifics of geometry of transmission, used materials, surface hardness of master links and rational durability of transmission. The geometric parameters of periodic race grooves and rolling elements are optimized by minimum contact stress and friction lost. The example calculation is given. The technique developed in addition to the analytical options presented in tabular and graphical form, where the unknown quantities are determined by the presented graphs and tables, allowing you to reduce the time to payment mechanism.
The development of optimized methodics of calculation of harmonic precessional drives with rolling elements
Keywords: периодическая дорожка качения; угол нутации; скольжение; оптимизация; harmonic drive; periodic race groove; nutation angle; sliding motion